Herpes simplex virus ophthalmic disease induced using two different methods of mice inoculation - Pereira,Sílvia Regina Ferreira Gonçalves (2001)
Two different procedures for inoculation of HSV on corneas of BALB/c mice were evaluated. The first was by the use of HSV suspensions directly on the corneas and the other was after corneal scarification. Animals by this later method presented greater morbidity and mortality than those of first group, suggesting that inoculation of HSV without scarification of the cornea should be the method of choice for the study of HSV ophthalmic infection. This model showed also be an efficient experimental system to testing antiviral drugs.